å¤ç”¸åˆä¸å¦æ ¡ä½¿ç”¨æ±‰è¯æ•™ææƒ…å†µåˆ†æž - Rohaini, Eka; Ina, Ina; Lusi, Lusi (Universitas Tanjungpura, 2024)
Three factors of Chinese language teaching are teacher, student, and teaching materials. Teaching materials are a crucial part of Chinese part of language learning. Some Chinese books published by Chinese publisher, some from indonesia, and others are written by teachers. For a deeper understanding of the utilization of Chinese Teaching Materials at Junior High School at Pontianak, the author conducted interviews with 13 schools. Then, combined with the specific use of Chinese Teaching Materials in Pontianak Junior High Schools, a statistical analisys divided into three points: 1. Analysis of the use of teaching materials from China, 2. Analysis of the use of teaching materials from Indonesia, 3. Analysis of teaching materials written by teachers. The results showed that the Teaching Materials from China used in Pontianak Junior High School were